The Role of Student Organization and Islamic Education in Cultivating Religious Moderation among Students - Giyono; Suyitno (Jurnal Praktik Baik Pembelajaran Sekolah dan Pesantren, 2025)
This article explores how Islamic Education (Pendidikan Agama Islam or PAI) teachers foster students' attitudes toward religious moderation as a unifying force for the nation. The study concludes that students at SMP Muhammadiyah 2 Tepus Gunungkidul, Indonesia (a private junior high school) actively participate in Rohis (Islamic Student Organization). This engagement is attributed to the students' educational backgrounds, as most are graduates of elementary schools in Gunungkidul, where mandatory programs include religious activities both in schools and their local communities. PAI teachers play a pivotal role in cultivating students' understanding and practice of religious moderation through both instructional and extracurricular Islamic activities. Under the guidance of these teachers and through the platform of school-based Islamic organizations such as Rohis, students engage in activities such as religious studies, social outreach programs, and initiatives to promote national unity and patriotism. These efforts serve as a foundation for fostering cohesion and solidarity among the nation's youth.